Modern Educational Technologies in Ukrainian High School - MYKHAYLISHYN, Halyna; LUTSAN, Nadiia; KONDUR, Oksana (Journal of Education, Technology and Computer Science, 2015)
The article deals with the problem of modern educational technologies in higher education. The general situation of establishment the modern educational technologies in Ukraine is outlined, which should contribute to the general development of the personality, the formation of ideological culture, individual experience, and creativity. The basic concept of „educational technology”, „learning technology”, „pedagogical technology” are analyzes. The attention is focused on the use of educational technology at the present stage in the learning process that significantly effects on the quality of training of qualified specialists.